Structure of the summer under fast ice microbial community near Syowa Station, eastern Antarctica - Ichinomiya, Mutsuo; Honda, Masaki; Shimoda, Haruto; Saito, Kenji; Odate, Tsuneo; Fukuchi, Mitsuo; Taniguchi, Akira (2007)
journal article